Design of an EnLite PCR assay for the Detection of Congenital Cytomegalovirus - Leppänen, Ossi (My University, 2020)
Congenital cytomegalovirus (CCMV) infection is a major cause of childhood disabilities. Human cytomegalovirus (HCMV) infection is mostly asymptomatic and the sequelae can form months or years later. These include sensorineural hearing loss (SNHL), visual impairment and intellectual disabilities. The chances of developing sequelae can be up to 25% in asymptomatic cases. With early detection the clinical outcome of the patients can be improved by antiviral drugs, speech therapy and cochlear implant. The aim of this work was to optimize the EnLite™ PCR for the detection of CCMV from a dried blood spots (DBS). The DBS used for optimization were spiked with the 1st World Health Organization (WHO) international standard for the human cytomegalovirus. The DBS are routinely taken from newborns and are easily preserved with a possibility of retrospective analysis. The assay was tested with the Quality control for molecular diagnostic (QCMD) 2015 panel. Different DBS elution methods were also compared. During the optimization, the main increase in amplification efficiency was achieved by changing the primer concentration from symmetric to asymmetric. The optimized dual-analyte assay detected 7/8 of the QCMD 2015 panel samples correctly, and the negative sample was negative. The one sample not recognized was reported to be infrequently detected by other laboratories which took part in this test panel. The assay competes very well against other PCR assays using the DBS as a sample format. Out of 275 anonymized leftover newborn DBS samples three CMV positives were detected. The assay can detect CMV DNA from newborn DBS samples. Different elution methods did not increase the detection frequency at low HCMV concentrations. Detection frequency at 500 IU/ml (appr. 455 copies/ml) of HCMV ranged from 30% to 40%. It is not possible to hit a detectable amount of virus with every 1.5 mm punch from the DBS of low viral concentration. At 1x103 IU/ml (appr. 900 copies/ml) of HCMV there is in theory 75 IU (appr. 68 copies/ml) of HCMV in one DBS and only around 1 IU (appr. 0.9 copies/ml) per 1.5 mm punch. Further testing is needed to determine the number of parallel samples required for the lowest possible detection limit for a feasible assay. Asymptomatic newborns with 12 000 copies/ml of HCMV DNA in blood have been reported to more likely suffer from sequelae, therefore the current detection limit should be enough for detection of most infected who are at risk of developing sequelae. Further sensitivity tests are required with patient samples with verified HCMV concentrations.